Pengaruh Terpaan Konten Erigo X JKT48 Pada Akun Tiktok @Erigo.Store Terhadap Keputusan Pembelian Produk Pakaian - Sofyan, Habib Ali; Utamidewi, Wahyu; Kusumaningrum, Rastri (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
Habib Ali Sofyan, 2010631190056. "The Influence of Erigo X JKT48 Content Exposure on the TikTok Account @Erigo.Store on Purchase Decisions for Clothing Products." Communication Science Study Program, Faculty of Social and Political Sciences, Singaperbangsa University, Karawang.The background of this research is TikTok as a popular social media platform in Indonesia, utilized by various brands, including Erigo, for marketing. One of its strategies is collaborating with JKT48 through the Erigo X JKT48 campaign, which attracts fans' attention. This study aims to analyze the influence of Erigo X JKT48 content exposure on the TikTok account @Erigo.store on purchasing decisions for clothing products.This study employs a quantitative approach with a causal method based on the philosophy of positivism, using the Uses and Effect theory by Sven Windahl. The research population consists of members of the TEAM48 Karawang community, with a sample size determined using the Isaac and Michael formula, resulting in 81 respondents. The findings indicate that exposure to Erigo X JKT48 content on the TikTok account @Erigo.store has a positive influence of 78.8% on fashion purchasing decisions, while 21.2% is influenced by other factors.